Methanogenic archaea and sulfate reducing bacteria co-cultured on acetate: teamwork or coexistence? - Ozuolmez, Derya; Na, Hyunsoo; Lever, Mark A.; Kjeldsen, Kasper U.; Jørgensen, Bo B.; Plugge, Caroline M. (Frontiers in Microbiology, 2015)
Acetate is a major product of fermentation processes and an important substrate for sulfate reducing bacteria and methanogenic archaea. Most studies on acetate catabolism by sulfate reducers and methanogens have used pure cultures. Less is known about acetate conversion by mixed pure cultures and the interactions between both groups. We tested interspecies hydrogen transfer and coexistence between marine methanogens and sulfate reducers using mixed pure cultures of two types of microorganisms. First, Desulfovibrio vulgaris subsp. vulgaris (DSM 1744), a hydrogenotrophic sulfate reducer, was cocultured together with the obligate aceticlastic methanogen Methanosaeta concilii using acetate as carbon and energy source. Next, Methanococcus maripaludis S2, an obligate H2- and formate-utilizing methanogen, was used as a partner organism to M. concilii in the presence of acetate. Finally, we performed a coexistence experiment between M. concilii and an acetotrophic sulfate reducer Desulfobacter latus AcSR2. Our results showed that D. vulgaris was able to reduce sulfate and grow from hydrogen leaked by M. concilii. In the other coculture, M. maripaludis was sustained by hydrogen leaked by M. concilii as revealed by qPCR. The growth of the two aceticlastic microbes indicated co-existence rather than competition. Altogether, our results indicate that H2 leaking from M. concilii could be used by efficient H2-scavengers. This metabolic trait, revealed from coculture studies, brings new insight to the metabolic flexibility of methanogens and sulfate reducers residing in marine environments in response to changing environmental conditions and community compositions. Using dedicated physiological studies we were able to unravel the occurrence of less obvious interactions between marine methanogens and sulfate-reducing bacteria.